Pengaruh Metode Rasm Utsmani terhadap Kelancaran dan Pemahaman membaca Al-Qur’an - Mustika Hadiyatun; Kholil Nawawi; Ibdalsyah Ibdalsyah (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
The ability to read the Qur'an at this time is very concerning because there are so many students who have not been able to read hijaiyah letters which is the basis for being able to read the Qur'an. Therefore, the Master should strive to provide the learning of the Qur'an with the proper methods. The purpose of this study was to find out the influence of the Ottoman rasm method on the smooth and understanding of reading the Qur'an of students. The methods in this study use an ex-Postfactoquantitative research approach. The results of this study are the ottoman rasm method is quite good towards the smooth reading of the Qur'an with statistical results obtained in 2023, while the ottoman rasm method of understanding falls into the moderate category with an overall average of 59%. There is a significant influence between the ottoman rasm method on the smooth reading of the Qur'an students at SDN Kedung Badak 3 Bogor City which includes a strong correlation between the ottoman rasm method and the smooth reading of the Qur'an students with statistical results obtained 0.721 which ranged from 0.60-0.799 and there was no significant influence between the ottoman rasm method on the understanding of reading the Qur'an students in SDN Kedung Badak 3 Bogor City including a very low correlation between the correlation between the ottoman rasm methods on the understanding of reading the Qur'an students in SDN Kedung Badak 3 Bogor City including a very low correlation between the Ottoman rasm method towards the understanding of reading Al-Qyour'an students with statistical results obtained 0.111 which ranges from 0.00-0.199 Keywords: Ottoman Rasm Method; smoothness; understanding